Short-term wealth effects of acquisition announcements by family-controlled firms in Malaysia - Ling, Yew Hua (Curtin University, 2014)
This study investigates whether Malaysian family-controlled firms create firm value when undertaking corporate acquisitions and which family-specific traits determine this value. Event study methodology is employed to examine the announcement-period wealth effect of corporate acquisition (cumulative abnormal returns – CAR). Inferences drawn in this study are based on 267-sample corporate acquisition announcements performed by publicly listed Malaysian family-controlled firms across a 10-year sample period from the years 2002 to 2011.